Trends in the management accounting research: A review of the literature published during the COVID-19 pandemic - Santos, M. R. C. (2021)
Management accounting theory aims to contribute to managers using accounting reports for supporting their management decisions. During the COVID-19 pandemic, such insights would be essential for supporting decisions during lockdowns and other policy makers’ rules imposed by this health crisis. To unveil how academic literature addresses management accounting challenges arising from the COVID-19 specific context, this study conducts an automated computer analysis of the bibliometric data addressing financial issues related to the COVID-19 pandemic.